Computational models in inflammatory bowel disease - Philippe Pinton (Wiley, 2022)
Abstract Inflammatory bowel disease (IBD) is a chronic and relapsing disease with multiple underlying influences and notable heterogeneity among its clinical and response‐to‐treatment phenotypes. There is no cure for IBD, and none of the currently available therapies have demonstrated clinical efficacies beyond 40%-60%. Data collected about its omics, pathogenesis, and treatment strategies have grown exponentially with time making IBD a prime candidate for artificial intelligence (AI) mediated discovery support. AI can be leveraged to further understand or identify IBD features to improve clinical outcomes. Various treatment candidates are currently under evaluation in clinical trials, offering further approaches and opportunities for increasing the efficacies of treatments. However, currently, therapeutic plans are largely determined using clinical features due to the lack of specific biomarkers, and it has become necessary to step into precision medicine to predict therapeutic responses to guarantee optimal treatment efficacy. This is accompanied by the application of AI and the development of multiscale hybrid models combining mechanistic approaches and machine learning. These models ultimately lead to the creation of digital twins of given patients delivering on the promise of precision dosing and tailored treatment. Interleukin‐6 (IL‐6) is a prominent cytokine in cell‐to‐cell communication in the inflammatory responses' regulation. Dysregulated IL‐6‐induced signaling leads to severe immunological or proliferative pathologies, such as IBD and colon cancer. This mini‐review explores multiscale models with the aim of predicting the response to therapy in IBD. Modeling IL‐6 biology and generating digital twins enhance the credibility of their prediction.